The Communication Strategy of the Wahdah Islamiyah Muslim Women's Institution in Promoting Da'wah Programs in the City of Makassar - Reni Angraeni AS; Mahmuddin; St. Nasriah (Jurnal Mercusuar, 2023)
The purpose of this study is to analyze the missionary program implemented by the Wahdah Islamiyah Muslim Women's Institution in Makassar City. The approach used in this study is a missionary and communication approach that emphasizes a deep understanding of a phenomenon that occurs from the aspect of the missionary model. This research is a qualitative descriptive type. Data in the study were collected by observation, interviews, and documentation. The results of this study found that the implementation of the missionary program of the Wahdah Islamiyah Muslim Women's Institution was carried out continuously, this was done so that the missionary program could be applied continuously. The missionary program of the Wahdah Islamiyah Muslim Women's Institution is; first, halaqah tarbiyah, is the acceptance of missionary material or in-depth religious studies conducted continuously and continuously. Second, dirosa or adult Quran education, this dirosa is done by mothers in studying the Quran. Third, Tahfidzul Quran or the memorization program, Fourth, the Majelis Taklim which aims to foster and develop polite and harmonious relationships between humans and Allah SWT. Fifth, Tabligh Akbar which is a major activity of the Wahdah Islamiyah Muslim Women's Institution.